Evaluasi Dampak Program Pelatihan Desain Grafis BLK Komunitas As Syifa Syech Yusuf di Kota Depok terhadap Alumni Peserta 2019-2020 - Ety Rahayu; Primadita Primadita (Pusat Penelitian dan Pengembangan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2021)
In order to prepare the availability of competitive and work-ready human resources from Islamic boarding schools to meet workforce needs, the Ministry of Manpower provides space for communities in Religious Education Institutions and/or Non-Government Religious Institutions to synergize in programs related to job training. The study aims to measure impact indicators and analyze the factors that influence the achievement of the impact of the Graphic Design Training Program at BLK Komunitas As Syifa Depok City based on aspects of input, activities and outcomes. This research is a summative evaluation with quantitative approach. The sampling technique used stratified random sampling as many as 84 samples to a population of 112 people. Data analysis in this research is descriptive univariate and bivariate, using SPSS for data processing. Bivariate analysis was conducted using cross tabulation with Chi-square (?2) test and Kendall’s Tau. Research concluded that impact indicators outcomes are as follows: 1) Working alumni are as much as 25 respondents (49%); and 2) Entrepreneurial alumni are as much as 5 respondents (9.8%). Whereas the rest are respondents with work status of not yet work for several reasons, such as proceeding on education as much as 10 respondents (19.6%) and or still looking for job vacancy as much as 11 respondents (21.6%). Indicators on outcome variables that affect the impact of the graphic design training program at BLKK As Syifa are Soft skills indicators and indicators of knowledge of business/work opportunities in the graphic design field.